Problematika Pembelajaran Maharah Qiraah Daring: Studi Kasus Terhadap Mahasiswa PBA IAIN Syaikh Abdurrahman Siddik Bangka Belitung - Ela Munawwaroh (IAIN Madura, 2021)
Online learning during this pandemic poses many problems. A common problem is that not all students have smartphones or a good network in their homes. Therefore, this study is intended to see more about what problems students face in learning reading skills. This study used a quantitative approach with descriptive methods. The subject of this research is students in the Arabic education program in the 4th semester. To collect data, the researcher used questionnaires and analyzed them using percentage techniques. The results of this research showed that the problems in learning reading skills faced by students of the Arabic education program IAIN SAS Bangka Belitung include: 1) Linguistic Aspect. More than 50% of students have poor language skills, especially in the mastery of nahwu and sharf, and 2) Non-linguistic Aspect. There are no significant problems, except for problems with the lost network caused by changes in weather or power outages.